Plasmonic-Resonant Bowtie Antenna for Carbon Nanotube Photodetectors - Hongzhi Chen; Ning Xi; King Wai Chiu Lai; Liangliang Chen; Carmen Kar Man Fung; Jianyong Lou (International Journal of Optics)
The design of bowtie antennas for carbon nanotube (CNT) photodetectors has been investigated. CNT photodetectors have shown outstanding performance by using CNT as sensing element. However, detection wavelength is much larger than the diameter of the CNT, resulting in small fill factor. Bowtie antenna can confine light into a subwavelength volume based on plasmonic resonance, thus integrating a bowtie antenna to CNT photodetectors can highly improve photoresponse of the detectors. The electric field enhancement of bowtie antennas was calculated using the device geometry by considering fabrication difficulties and photodetector structure. It is shown that the electric field intensity enhancement increased exponentially with distance reduction between the CNT photodetector to the antenna. A redshift of the peak resonance wavelength is predicted due to the increase of tip angles of the bowtie antennas. Experimental results showed that photocurrent enhancement agreed well with theoretical calculations. Bowtie antennas may find wide applications in nanoscale photonic sensors.